POLA MAKAN DAN UKURAN LINGKAR LENGAN ATAS (LILA) IBU HAMIL YANG MEMILIKI RISIKO PERSALINAN SECARA SECTIO CAESAREA DI PUSKESMAS STABAT KABUPATEN LANGKAT - Nila Tuti Safitri; Fitri Ardiani; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
The labor risk by Sectio Caesarea is one of which can be caused by nutritional problems.Pregnant women with less or more nutritional status it can pose a number risks to the her fetus, pregnancy, and childbirth. So it’s necessary to control a good dietary habit and appropriate during her pregnancy. This research was aimed to know the description of dietary habit and the nutritional status of pregnant women who has a risk of delivery by Sectio Caesarea at Puskesmas Stabat Kabupaten Langkat. Type of this research was observational with cross sectional research design. This research was conducted in Puskesmas Stabat Kabupaten Langkat there was 42 pregnant women who had a risk of caesarean delivery was used total sampling technique. Assessment of food structure, calculate energy and protein consumption was conducted by using 24 hour food recall method. Measuring upper arm circumference of pregnant women which was used by the upper arm circumference tape. Data analysis was used descriptive analysis. The result of this research showed that most of the food composition of pregnant women 83,3 % was not complete, Energy consumption 57,1% was less category and Protein consumption 54.8% was good category. Pregnant women consumed rice as a main food. Most of pregnancies eat wet fish and tempe as side dish, spinach and kale as a vegetables, then banana and papaya as a fruit. Upper arm circumference 85,7% was normal category. It’s suggested to the pregnant woment who have nutritional status problem to be more careful about their food patterns and nutrisonal status during pregnancy, and to the health personnel that are public health center to provide nutrition counseling about diet settings to the pregnant women. And mobilize and improve the monitoring of nutritional status of pregnant women in their working area. Keywords: Food Pattern, Nutritional Status, Pregnant Women, Sectio Caesarea